Growing managers : moving from team member to team leader - Ellington-Booth, Brenda (SAGE knowledge. Cases., 2016)
This case describes a newly promoted middle manager in a global, multi-cultural organization who is challenged by a number of factors in the workplace which are impacting her and her team's ability to perform. While it would be easy to blame the new manager, deeper analysis in fact reveals that many forces are at work here in addition to her inexperience, including communication of strategy and performance objectives, mismanaged team members, cultural inconsistencies and a lack of leadership direction and/or skill from the very top.